Análisis de la comercialización de la empresa industria cartonera ecuatoriana en la ciudad de Guayaquil, Ecuador - Cagua Alvarado, Heidy Lisbeth (2024)
We can consider the paper industry as a useful development activity because many industries or markets depend on the production of corrugated cardboard products. Thanks to this product, the company managed to position itself in the market, for many reasons, one of which is the quality of its products. The company is interested in the durability and quality of its products, we need a quality study to study and determine the composition of the paper in order to convince customers of our products and achieve market position on its merits. In the first chapter we managed to establish general and specific objectives, which show the main questions and lines of research in which we can identify the reflection on the protection of the main questions, including: What factors influence this basis on the position of the company in the market? This will be analyzed through its customers from the high market, such as bananas, to the low market, such as machinery. The second chapter is: Theoretical framework and background of the problem, which suggests that economic theory can be best studied in market relations under law and legal frameworks. The research methods in Chapters 3 and 4 determine the nature of the research, i.e., mixed methods, because quantitative and qualitative methods are used in the analysis to find in the surveys and interviews what are the.